1983
DOI: 10.1111/j.1365-2621.1983.tb10814.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Changes in Blue Crabs (Callinectes sapidus) During Cooking

Abstract: The change from the blue-green color to the red-orange color of Blue crabs was monitored during cooking using a Hunterlab Color Difference Meter set in the L, a, b scale. Changes in the "a" readings were correlated with the changes in internal body temperature. A cooking temperature of 100°C resulted in maximum red-orange color development after 30 set with no significant changes occurring subsequently. The internal body temperature of the crabs was shown to be only slightly above the initial temperature when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Like in other crustaceans, muscle color of crabs changes markedly during heating (Fox ,1976;Himelbloom et al, 1983;Gates et al, 1993;Chaiyawat et al, 2008;Parisenti et al, 2011).…”
Section: Color Changes During Thermal Treatment In the Coldest Point mentioning
confidence: 96%
“…Like in other crustaceans, muscle color of crabs changes markedly during heating (Fox ,1976;Himelbloom et al, 1983;Gates et al, 1993;Chaiyawat et al, 2008;Parisenti et al, 2011).…”
Section: Color Changes During Thermal Treatment In the Coldest Point mentioning
confidence: 96%
“…Some processors have employed color change and indices to identify the termination of a boiling process. However, research has shown that the internal temperature of some crab species was only slightly above the initial temperature when maximum color development occurred (Himmelbloom et al, 1983). Processors should be aware that non-uniform steam distribution and large temperature differences are frequently found within the retort during pressure cooking.…”
Section: Slaughter/cookingmentioning
confidence: 98%
“…faculty, staff, and students experienced in sensory work with crawfish meat. Triangle tests, as described by Larmond (1977), were used to determine differences between species. Approximately 6g samples of crawfish meat at room temperature were placed in small paper cups, labeled with random 3-digit codes, and served on paper plates.…”
Section: Source and Cooking Of Crawfishmentioning
confidence: 99%
“…This was followed by unwashed meat presented in a like manner. Larmond's (1977) tables for rapid analysis of triangle data were used to analyze the data. Live red swamp and white river crawfish were obtained from a local seafood processor on three occasions.…”
Section: Source and Cooking Of Crawfishmentioning
confidence: 99%